Analysis of provisions and contingent liabilities in companies listed on B3 - Gabriella Janete Espindula; Maíra Melo de Souza (Revista Ambiente Contábil)
Purpose: Analyze the level of mandatory and voluntary disclosure of provisions and contingent liabilities in Brazilian publicly traded companies.